Aging premium choice chuck rolls for minimal days maximizes color stability and extends retail display life - Garner, C. M.; Unruh, John A.; Hunt, Melvin C.; Boyle, Elizabeth A. E.; Houser, Terry A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Subprimals can be stored in a vacuum package for extended periods of time. The number of days that subprimals may be held before processing can be influenced by the distribution chain, accessibility, and subprimal price fluctuations. Extended vacuum storage before grinding could affect biochemical, oxidative, and microbial properties of these subprimals and influence their color stability. Our objective was to determine the effects of two subprimal types (chuck roll and knuckle), two quality grades (Premium Choice and Select), and three vacuum-packaged storage aging times before processing (7, 21, and 42 days) on ground beef patty display color stability.
Keywords: Beef; Ground beef; Vacuum storage; Subprimals; Quality grades